2012
DOI: 10.1210/en.2011-1733
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Channel Mutant KCNJ5 T158A Expression in HAC-15 Cells Increases Aldosterone Synthesis

Abstract: Primary aldosteronism is the most common cause of secondary hypertension, most frequently due to an aldosterone-producing adenoma or idiopathic hyperaldosteronism. Somatic mutations of the potassium channel KCNJ5 in the region of the selectivity filter have been found in a significant number of aldosterone-producing adenomas. There are also familial forms of primary aldosteronism, one of which, familial hyperaldosteronism type 3 which to date has been found in one family who presented with a severe abnormality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(155 citation statements)
references
References 45 publications
9
145
0
1
Order By: Relevance
“…However, both of these ZG/ZF-like cells strongly express CYP11B2, consistent with autonomous aldosterone production in APCCs. Recurrent mutations observed in APA are known to cause aldosterone overproduction in in vitro experiments (8,12); therefore, the existence of these mutations in APCCs supports autonomous aldosterone production. Of note, we identified distinct somatic mutations in individual APCCs from the same adrenal gland, which is in contrast to previously studied APAs that have been reported to harbor a single mutation driving aldosterone production.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, both of these ZG/ZF-like cells strongly express CYP11B2, consistent with autonomous aldosterone production in APCCs. Recurrent mutations observed in APA are known to cause aldosterone overproduction in in vitro experiments (8,12); therefore, the existence of these mutations in APCCs supports autonomous aldosterone production. Of note, we identified distinct somatic mutations in individual APCCs from the same adrenal gland, which is in contrast to previously studied APAs that have been reported to harbor a single mutation driving aldosterone production.…”
Section: Discussionmentioning
confidence: 97%
“…Germ-line KCNJ5 mutations were also identified as the cause of FHIII (7, 11). KCNJ5 mutations cause pathologic conductivity of Na + ions, cell depolarization, and increased intracellular Ca 2+ , which results in CYP11B2 expression and aldosterone hypersecretion (7,8,11,12). In addition to KCNJ5 mutations, ATPase, Na + /K + transporting, α1-polypeptide (ATP1A1); ATPase, Ca 2+ -transporting, plasma membrane 3 (ATP2B3), and calcium channel, voltage-dependent, L-type, α1D-subunit (CACNA1D) mutations have been found in an additional ∼15% of APA (10,13,14).…”
mentioning
confidence: 99%
“…The hot spots of the point mutation in the KCNJ5 gene are reported as G151R and L168R (Choi et al 2011). By using in vitro study, Oki et al (2012) demonstrated that a mutation of KCNJ5 (T158A) resulted in decreased ion selectivity of the channel, membrane depolarization, activation of voltage-gated Ca 2+ channels, and increased intracellular Ca 2+ concentration, CYP11B2 overexpression, and aldosterone production. We also have demonstrated that the relative expression levels of CYP11B2 and HSD3B1 mRNAs were significantly higher in KCNJ5-mutated APA (G151R or L168R) than in APA without the KCNJ5 mutilation, while the mRNA of cytochrome P450 17α-hydroxy/17,20-lyase (CYP17A1), a microsomal enzyme essential for the biosynthesis of adrenal and gonadal steroids, was significantly higher in APA without the KCNJ5 mutation than in KCNJ5-mutated APA (G151R or L168R) (Konosu-Fukaya et al 2015).…”
Section: Somatic Mutations In Aldosterone-driver Genes and Cyp11b2 Exmentioning
confidence: 99%
“…Recent studies have developed several analytical methods and revealed many novel and key findings regarding the molecular pathogenesis of APA, especially the upregulation system of aldosterone synthase (CYP11B2) expression in APA (Oki et al 2012;Beuschlein et al 2013;Scholl et al 2013;Nakamura et al 2014b;Hattangady et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Comme c'est le cas pour les mutations somatiques décrites dans les adénomes produisant de l'aldostérone, cette mutation est localisée à proximité du motif GYG qui confère à GIRK4 sa sélectivité pour le K + . Comme les autres mutations, celle-ci entraîne une perte de sélectivité pour le K + et un influx de Na + dans la cellule résultant en une dépolarisation de la membrane plasmique et une activation de canaux Ca 2+ dépendants du voltage, conduisant à une accumulation de Ca 2+ intracellulaire [13]. Différentes autres mutations germinales de KCNJ5 ont été décrites dans des familles de type FH-III.…”
Section: Anomalies De Kcnj5 Dans L'hyperaldostéronisme Primaire Familialunclassified